Establishment of a regeneration system through callus formation and genetic analysis based on rapd for detection of somaclonal variation in dendrobium serdang beauty - Khosravi, Alireza (2008)
Flowers of the Orchidaceae family are highly variable in shape, color and smell, which make orchids the most important cut flowers in the market. Among the orchid varieties, Dendrobium hybrids have high regards in the cut flower industry. This study was aimed at establishing a plant regeneration system of Dendrobium Serdang Beauty and the characterization of colchicine-induced mutation by RAPD. The first part of the study was to develop a plantlet regeneration system for D. Serdang Beauty. Callus was induced from protocorm- like bodies (plbs), and cultured on media supplemented with different auxins of various concentrations for plantlet regeneration. Highest fresh weight in callus induction and proliferation was obtained on MS medium containing 1.5 mg/L IBA. Calli proliferated on medium supplemented with 1.5 mg/L IBA were used as explants for plantlet regeneration. The highest percentage of plantlet regeneration was obtained in treatments with 1 mg/L KIN and 1.5 mg/L NAA (90%). In the acclimatization study, plants were cultured in vivo in different media under the same environment. All media gave high percentage of plant survival. Medium M1 (charcoal), M2 (charcoal mixed with broken rock) and M5 (sawdust mixed with charcoal) produced the highest percentage of plant survival (100%). Following the callus induction study, calli obtained were cultured on media containing different concentrations of colchicine (0, 5, 10, 20 and 25 mg/L). Colchicine treatment at 5 mg/L significantly gave the highest fresh weight of regenerated plantlets (3.43 g). Subsequently, the resulting calli from colchicine treatments were analyzed for somaclonal variation and characterized using RAPD. The study indicated that somaclonal variation existed and was polymorphic in nature. Based on the analysis, D. Serdang Beauty V showed 25% differentiation with the mother plant. In a further analysis, D. Serdang Beauty V was also characterized with other Dendrobium species. D. Serdang Beauty V showed high dissimilarity with other Dendrobium varieties.In conclusion, the result showed that IBA in low concentration was effective to induce and proliferate more callus. In the regeneration study, KIN alone or in combination with other auxin was useful to regenerate more plantlets. Meanwhile in the acclimatization study, charcoal was useful to growth of Dendrobium. Also colchicine induced mutation method was useful for the production of mutated Dendrobium and the RAPD technique appeared to be useful for the detection of variation between species and varieties